Synergistic stabilization of a clean-label bigel: whey protein isolate constructing dual oleogel/hydrogel networks - Run-Hao Fu; Han Tao; Bao-Cai Xu; Ran Feng; Bao Zhang (Food Hydrocolloids, 2026)

Investigating the therapeutic effects of injectable ammonium glycyrrhizate hydrogel co-loaded with doxorubicin and ATP in triple negative breast cancer - Wanying Chen; Xinyu Liu; Tiantian Guo; Keneng Cai; Wenli Cai; Run Xia; Mengyao Xu; Weichi Jiang; Chuyi Yu; Jianjia Feng; Chengli Ling; Sheng Zhou; et al. (Chemical Engineering Journal, 2026)

Environmental cadmium disrupts placental angiogenesis and fetal growth via enhancing m6A modification in Wwp2 - Cheng-Fang Sun; Ye-Xin Luo; Xin-Xin Zhang; Rui Pan; Yu-Xi Wu; Jia-Ying Chen; Xin-Run Wang; Lan-Lan Wu; Si-Ting Liu; Wei Chang; Zhi Yuan; Da-Min Zhu; et al. (Environmental Pollution, 2026)

Nocturnal ozone enhancement in China: Long-term trends and the roles of daytime ozone and nocturnal meteorology - Min Wu; Run Liu; Feng Tan; Zhenying Ye; Jingwen Zhang; Jing Chen; Wenbo Wu; Guoxin Chen (Atmospheric Pollution Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

A new chlorine-containing flavanol and four new phenylpropanoids from Toddalia asiatica - Bing-Ying Zheng; Zhan-Tao Zhao; Feng Wu; Nan An; Shu-Qi Wu; Lu Gan; Sheng Yin; Run-Zhu Fan; Gui-Hua Tang (Natural Product Research, 2026)

Extent of soil disturbance and spatial strength degradation induced by spudcan penetration and extraction in clay - Cheng-feng Li; Rui Zhou; Run Liu; Hai-yang Zhang; Peng-cheng Ma (Ocean Engineering, 2026)

Dexmedetomidine inhibits microglia ferroptosis to relieve postoperative cognitive dysfunction in elderly rats through JPX/HIF-1/DHODH pathway - Yunfei Wang; Feng Ouyang; Run Feng; Zhe Ding; Jiafang Wang (Experimental Brain Research, 2026)

Pleurotus citrinopileatus polysaccharide inhibits glioma growth by downregulating the expression of CHI3L1--- CHI3L1 as a therapeutic target in glioma - Nuo-Ling Ye; Bing-Bo Zhuang; Hao-Dong Chen; Run-Qi Zou; Gang-Feng Cai; Jin-Hai Huang; Han Meng; Chun-Hua Wang; Jing Chen (Food and Bioproducts Processing, 2026)

Defect-passivated Te-doped Cs2HfCl6 perovskite microcrystals with high efficiency and robust stability for X-ray imaging - Yanqing Zu; Run Gan; Lixia Jing; Bing Yang; Binglin Zeng; Liru Yuan; Peitao Liu; Xiaodong Li; Ailing Feng; Lei Zhou (Chemical Engineering Journal, 2026)

From species to therapeutic property: distribution differences of threatened Chinese medicinal plants under climate change - Yun-Han Chen; Rui Yang; Run-Han Jiang; Yu Xia; Ling-Feng Mao (Biodiversity and Conservation, 2026)

Gram-scale photocatalytic benzyl alcohol oxidation via photon-heteroatom jointly promoted redox cycling over nickel-based Pickering emulsion - Shihao Du; Run Shi; Gongao Peng; Jiaqi Zhao; Lingsong Wang; Feng Ryan Wang; Tierui Zhang (Science Bulletin, 2026)

CARE: a next-generation high resolution cloud and radiation remote sensing product and its Earth system applications - Husi Letu; Huazhe Shang; Run Ma; Chong Shi; Takashi Y. Nakajima; Hiroshi Ishimoto; Jérôme Riedi; Lesi Wei; Ri Xu; Dabin Ji; Qixiang Sun; Sude Bilige; et al. (Science Bulletin, 2026)

Orchestrating the continuous self-circulating granular sludge process: An intelligent platform for real-time adaptive control - Wei-Kang Qi; Yue-Mei Wu; Wei Xu; Run-Feng Tian; Cong Wang; Yong-Zhen Peng; Shu-Jun Zhang (Water Research, 2026)

Structural and textural enhancement of oleogels via l-lysine-mediated whey protein cryogel modification - Run-Hao Fu; Ran Feng; Si-jie Wu; Bao-Cai Xu; Bao Zhang (Food Chemistry, 2026)

Observational evidence of ionospheric feedback effect in generating throat aurora - Huixuan Qiu; Desheng Han; Yong Wang; Qiang Zhang; Huiting Feng; Run Shi; Shunrong Zhang; Zhiwei Wang; Yongliang Zhang (Science China Earth Sciences, 2026)

Electro-triggered interfacial reconfiguration for automatic membrane fouling cleaning: Fighting surfactants with surfactants - Di Zhao; Kaiming Peng; Liya Wang; Run Jiang; Xinyuan Peng; Feng Zheng; Xiangfeng Huang; Chen Cai; Jia Liu; Zhiping Cai (Water Research, 2026)

Study on the dynamic response and system reliability of curved beam bridge under multi-dimensional non-uniform random earthquake excitation - Xi-mei Li; Peng-hui Fan; Wan-run Li; Yong-feng Du (Soil Dynamics and Earthquake Engineering, 2026)

Numerical investigation on combustion behavior of an X-type rotary engine: Impact of hydrogen enrichment and engine speed - Run Zou; Lei Zhang; Ting Hou; Yanhong Zhou; Wei Yang; Lijun Lei; Feng Li (Fuel, 2026)

Ultrasensitive detection of α-amanitin using a dual-signal aptasensor based on aptamers selected via a novel MB-GO SELEX strategy - Run Tian; Jiadi Sun; Xinqiang Xie; Wangqiu Deng; Mengyao Zheng; Yongli Ye; Yongwei Feng; Xiulan Sun (Food Bioscience, 2026)

Autophagy, ROS, and their interplay in plant adaptive responses - Chi Zhang; Song-Qi Li; Pengwei Jing; Run-Xin Wu; Yu-Qing Ma; Ji-Xiao Wu; Ru-Feng Song; Wen-Cheng Liu (Journal of Plant Physiology, 2026)

Dynamic oil fume exhaust method and calculation formula suitable for residential kitchens in cold regions - Kailiang Huang; Run Bai; Guohui Feng; Xiaoxu Li; Chaoying Fan; Helu Cao; Haipeng Yu (Building and Environment, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

Oral Administrations of Short-Chain Fatty Acids or Probiotics Extend the Survival Times and Mitigate the Neuropathological Damages in the Scrapie-Infected Hamsters - Yuan Wang; Dong-Lin Liang; Run-Dong Cao; Ruhan A.; Jia-Feng Zeng; Bing Xu; Ju-Zheng Li; Wei-Wei Zhang; Li-Ping Gao; Kang Xiao; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Decaprenyl diphosphate synthases in Monolepta hieroglyphica: DPPS-mediated CoQ biosynthesis impacts juvenile hormone and gut microbiota - Xuan Song; Jun-feng Kou; Chang Liu; Yong Yang; Da-wei Zhang; Chao-qun Yi; Wen-tao Liu; Run Chen; Wei-hao Guo; Yue-qin Wang; Tian-tao Zhang; Yong-jun Zhang (Insect Biochemistry and Molecular Biology, 2025)

Geological and geochemical characteristics of intermediate-basic intrusions in Funiushan area, southern margin of the North China Craton: Implications for tectonic environment and mantle properties in the Early Cretaceous - Wei Zeng; Feng-Yue Sun; Cheng-Dong Li; Zhi-Dan Li; Yin-Hang Cheng; Wen-Gang Liu; Jia-Run Tu; Chao Zhang; Xing Liu; Wei-Zhi Sun (Lithos, 2025)

Bond behavior between concrete and thermoplastic GFRP bars with novel surface features - Jun-Jie Zeng; Hou-Qi Sun; Jun-Run Xia; Sheng-Zhao Feng; Bin Zhao; Jie-Kai Zhou; Yan Zhuge (Engineering Structures, 2025)

Dual-gripper coordination effect stabilizing zinc anodes for high-performance zinc metal batteries - Tian-Yi Yang; Kun Li; Ting-Ting Su; Li Ma; Qiu-Shuai Xu; Chang-You Shao; Wen-Feng Ren; Run-Cang Sun (Chemical Engineering Journal, 2025)

Formation mechanisms of carcinogenic N-nitrosamines from dissolved organic matter derived from nitrogen-containing microplastics during chloramine disinfection - Run Zhou; Kecheng Zhu; Zhuo Gao; Xuemin Feng; Qian Hu; Lingyan Zhu (Water Research, 2025)

A review of pharmacological effects and bioactive constituents of Euonymus alatus - Na Sun; Yujing Wang; Caihong Zhou; Huanhuan Kang; Run Wang; Xiu Feng; Shuo Ma; Linxuan Jin; Xin Zhang; Penghua Shu (Phytochemistry Letters, 2025)

Advancing phylogenomic marker design: Updated USCO and UCE databases of Collembola - Shiyu Du; Shengyang Zhang; Run Jiang; Daoyuan Yu; Nerivânia Nunes Godeiro; Feng Zhang (Zoologica Scripta, 2025)
Molecular markers are critical for elucidating the evolution and genetic diversity of species. The relentless progress and innovation in sequencing technology have enabled the acquisition of a vast repository of high‐quality organism genomic data. A more precise and high‐resolution set of molecular markers can provide deeper insights into species evolution. Collembola, as a key group of soil arthropods, has been the focus of extensive research due to its evolutionary and ecological importance. Recently, several chromosome‐level genomes of springtails have been sequenced. Our objective was to enhance molecular marker design to improve the accuracy and robustness of the Collembola database, focusing on universal single‐copy orthologues (USCOs) and ultraconserved elements (UCEs). We constructed a set of 4073 USCOs by examining 15 genomes, including 11 high‐quality genome data at the chromosome level. We then curated and adapted a customized BUSCO (Benchmarking Universal Single‐Copy Orthologues) dataset specifically designed for USCO evaluation. In addition, we developed a novel probe set for UCEs, comprising 67,707 baits targeting 2608 specific loci. We achieved the successful capture of 2089–3847 USCOs and 972–1405 UCEs across the 15 genomes under investigation. These markers were tested to assess their capture success and systematically validated against two previous phylogenomic studies. This approach is instrumental in species identification, phylogenomics, population genetics, and contributes significantly to advancing our understanding of evolutionary biology and ecology. Both datasets are freely available for download from figshare: https://doi.org/10.6084/m9.figshare.26839783 .

Aptamer-modulated Pt/Au/MIL-100(Fe) nanozymatic activity for the colorimetric detection of deoxynivalenol in grains - Huang Dai; Junlan Yu; Run Zhou; Guijie Hao; Zhaohui Qiao; Zhe Feng; Xin Liu; Jie Bi; Jiahua Wang; Xiaodan Liu; Fuwei Pi; Yafang Shen (Food Chemistry, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Enhanced activation of peroxymonosulfate by nickel sulfide with sulfur vacancies for ultrafast organic pollutants degradation: Roles of active sites and mechanism - Cai-Wu Luo; Liang Jiang; Xian-Feng Li; Qiang-Mao Wan; Tian-Jiao Jiang; Sen-Ping Mao; Jing-Qian Guo; Run-Ze Zhao; Chao Xie (Environmental Pollution, 2025)

Study on methane flux variation characteristics and regulation mechanisms in urban wetlands under different restoration years and moisture gradients - Qing Liu; Chun Feng; Run Li; Yun Zhou; Xin Meng; Hua Liu (Environmental Research, 2025)

Synergistic effects of ether oxygen bond/benzene ring and hydrocarbon chain structure on soot morphology and nanostructure - Wenlong Dong; Run Hong; Shunjie Feng; Bingbing Qiu; Ruiming Fang; Huaqiang Chu (Fuel, 2025)

Effect of ignition timing on combustion characteristics and emissions of an X-type rotary engine with the high efficiency hybrid cycle - Run Zou; Feng Li; Jinxiang Liu; Wei Yang; Lijun Lei; Lei Zhang (Fuel, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Evaluating a hybrid process of anaerobic digestion, aerobic degradation, and electrochemical separation for swine wastewater treatment with methane and nutrient recovery - Run-Feng Chen; Chun-Hai Wei; Hai-Tao Zhong; Xiu-Feng Ye; Jun-Jie Ye; Kai Liu; Quan-Bao Zhao; Huu Hao Ngo (Biosystems Engineering, 2024)

Biomagnification of polybrominated diphenyl ethers and alternative halogenated flame retardants through food chains of yellowfin tuna (Thunnus albacares) and their prey from the South China Sea and the associated potential health risk - Run-Xia Sun; Chang-Gui Pan; Feng-Jiao Peng; Zhong-Biao Chen; Yue Sun; Jiang-Tao Fan; Jun Zhang; Bi-Xian Mai (Science of The Total Environment, 2024)

Large-scale penetration model tests of bucket foundations of different structural types in clay - Xiangchuan Meng; Run Liu; Guangsi Chen; Jijian Lian; Feng Wen (Ocean Engineering, 2024)

Metal-support interaction manipulate the sulfidation and morphology of MoS2 slabs with dominant double-layer structure via surfactant assistance for CO hydrogenation to higher alcohols - Yihua Cao; Xueli Yin; Yonghao Gan; Run Cai; Qi Wang; Bo Feng; Yindan Wu; Likun Wen; Yichen Song; Xiaoping Dai (Fuel, 2024)

Evidence of polybrominated diphenyl ethers (PBDEs) and alternative halogenated flame retardants (AHFRs) in wild fish species from the remote tropical marine environment, south China sea - Run-Xia Sun; Chang-Gui Pan; Feng-Jiao Peng; Zi-Ling Yu; Hai-Yang Shao; Bing-Zhong Yang; Zhong-Biao Chen; Bi-Xian Mai (Environmental Pollution, 2024)

Novel separate aeration self-circulating technology for continuous aerobic granular sludge process: Performance evaluation, hydrodynamic simulation and control strategy - Wei-Kang Qi; Run-Feng Tian; Bo Li; Shu-Jun Zhang; Yong-Zhen Peng; Cong Wang (Water Research, 2024)

Structurally diverse diterpenoids from the seeds of Caesalpinia minax Hance and their bioactivities - Wen-Chao Tu; Lin-Fen Ding; Liu-Dong Song; Yong-Jiao Li; Run-Cheng Yan; Yun Wu; Wei-Yang Feng; Xing-De Wu (Phytochemistry, 2024)

Ecotoxicological assessment, oxidative response, and enzyme activity disorder of the rotifer Brachionus asplanchnoidis exposed to a toxic cocktail of spent lithium-ion battery leachate - Yi-fan Feng; Yu Zhang; Run-jia Yang; Si-qi Li; Xiao-jie Liu; Cui Han; Yi-fu Xing; Jia-xin Yang (Journal of Hazardous Materials, 2024)

Tailoring porosity and acidity of In-Situ Mg-B-Dual-Modified ZSM-5 zeolite for benzene alkylation with methanol to toluene and xylene - Run Cai; Qi Wang; Yutai Liang; Yonghao Gan; Yihua Cao; Bo Feng; Yindan Wu; Xiaoping Dai (Fuel, 2024)

Plasma Deoxycholic Acid Levels are Associated with Hemodynamic and Clinical Outcomes in Acute Pulmonary Embolism Patients - Na Sun; Yi-Qiang Chen; Yan-Sheng Chen; Lei Gao; Run-Wei Deng; Jing Huang; You-Li Fan; Xuan Gao; Bin-Feng Sun; Na-Na Dong; Bo Yu; Xia Gu; et al. (Cardiovascular Toxicology, 2024)

Numerical modelling of sand liquefaction via a weakly coupled approach between lattice spring and discrete element methods - Zhe Li; Gao-Feng Zhao; Yu-Jie Zhang; Zhi-Peng Hao; Kai-Li Niu; Run Liu (Computers and Geotechnics, 2024)

Liquid metal micrometer fibers with chain-bead structure for precision sewing in smart textiles applications - Feng Xu; Huiyun Xiao; Yuanzhao Wu; Fali Li; Haifeng Zhang; Jinyun Liu; Zidong He; Shiying Li; Qi Zhang; Xingjian Lu; Jie Shang; Yiwei Liu; et al. (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

A Four Amino Acid Metabolism-Associated Genes (AMGs) Signature for Predicting Overall Survival Outcomes and Immunotherapeutic Efficacy in Hepatocellular Carcinoma - Lu-sheng Liao; Zi-jun Xiao; Jun-li Wang; Ting-jun Liu; Feng-die Huang; Yan-ping Zhong; Xin Zhang; Ke-heng Chen; Run-lei Du; Ming-you Dong (Biochemical Genetics, 2024)

Ordered mesoporous Mg-modified silica to confine MoS2 slabs with high sulfidation and dispersion for higher alcohol synthesis via CO hydrogenation - Ziteng Ren; Yihua Cao; Xueli Yin; Yonghao Gan; Run Cai; Qi Wang; Bo Feng; Yindan Wu; Xiaoping Dai (Fuel, 2024)

Advances in biotin biosynthesis and biotechnological production in microorganisms - Jia-Run Zhao; Si-Qi Zuo; Feng Xiao; Feng-Zhu Guo; Lu-Yi Chen; Ke Bi; Dong-Yuan Cheng; Zhi-Nan Xu (World Journal of Microbiology and Biotechnology, 2024)

Identification, distribution, bactericidal and immunoregulatory activities of NK-lysins in grass carp (Ctenopharyngodon idella) - Gai Ling Wang; En Zhong Li; Da Hong Li; Ming Cheng Wang; Shan Shan Sun; Run Yan Xiong; Chuan Feng Li; Bao Jian Sun; Hai Xia Xie (Aquaculture, 2024)

Effects of ammonia addition on soot formation in hydrocarbon fuels combustion: Challenges and prospects - Huaqiang Chu; Shunjie Feng; Run Hong; Xiaoyan Ma; Fen Qiao; Longfei Chen (Fuel, 2024)

Fluctuations of Qiangyong glacier in southern Tibetan Plateau over the past 500 years recorded by proglacial lacustrine sediments - Run Zhang; Qi Feng; Fei Zhang; Le Li; Yang Xu; Zhangdong Jin (Quaternary International, 2024)

Effect of NH3 addition on soot morphology and nanostructure evolution in laminar ethylene diffusion flame - Shunjie Feng; Run Hong; Jiawei Qi; Wenlong Dong; Bingbing Qiu; Xianyao Yan; Huaqiang Chu (Fuel, 2023)

Isolation and Identification of a Phosphate-Solubilizing Pantoea dispersa with a Saline–Alkali Tolerance and Analysis of Its Growth-Promoting Effects on Silage Maize Under Saline–Alkali Field Conditions - Ying Cui; Yujie Zhao; Run Cai; Hao Zhou; Jiaxin Chen; Lirong Feng; Changhong Guo; Dan Wang (Current Microbiology, 2023)

Soot formation in high-pressure combustion: Status and challenges - Huaqiang Chu; Jiawei Qi; Shunjie Feng; Wenlong Dong; Run Hong; Bingbing Qiu; Weiwei Han (Fuel, 2023)

Overexpression of OsNF-YB4 leads to flowering early, improving photosynthesis and better grain yield in hybrid rice - Meifang Peng; Feng Gan; Xiaomin Lin; Run Yang; Shaoyi Li; Wei Li; Lan Wu; Xiaoli Fan; Kegui Chen (Plant Science, 2023)

LC-MS Based Metabolomic Profiling of Largehead Hairtail (Trichiurus japonicus) Ovary Reveals Metabolic Signatures of Ovarian Developmental Process (II–IV) - Liu-Ying Feng; Li-Ping Yan; Run-Wei Li; Sheng-Fa Li; Jia-Hua Cheng; Yan Jin (Fishes, 2023)
Trichiurus japonicus is an economically important fish that ranks 11th in global marine fish capture production. However, the reproductive characteristics of this fish have undergone notable changes in recent decades, potentially affecting the quality of offspring and sustainable utilization. To improve our understanding of the physiological regulation of maturation in T. japonicus, untargeted liquid chromatography mass spectrometry was utilized to identify the small molecules that characterize the comprehensive metabolic profiles of ovaries during ovary development from stage II to stage IV. According to the results of OPLS-DA, the ovarian metabolite profiles of the three developmental stages were separated. The concentrations of 124 and 100 metabolites were significantly altered between stage II vs. III and III vs. IV, respectively. Lipids and lipid-like molecules accounted for the largest proportion of the altered metabolites, followed by amino acids, peptides, and analogues. The significantly altered metabolites-enriched pathways differed slightly between stages II and III and stages III and IV. Steroid-related pathways were heavily affected during stages II to III, while significantly altered metabolites from stages III to IV were involved in oocyte-maturation-related pathways. Through metabonomics analysis, potentially important metabolic pathways and metabolites between different ovarian stages were detected, providing basic information for further investigation of maturation mechanisms in wild fish.

Failure mechanism of a large-scale composite deposits caused by the water level increases - Xin Zhang; Guo-xiang Tu; Qi-feng Luo; Hao Tang; Yu-lin Zhang; An-run Li (Journal of Mountain Science, 2023)

How much urban air quality is affected by local emissions: A unique case study from a megacity in the Pearl River Delta, China - Meng-Xue Tang; Xiao-Feng Huang; Pei-Ting Yao; Run-Hua Wang; Zhi-Jie Li; Chao-Xi Liang; Xing Peng; Li-Ming Cao; Ke Du; Kuangyou Yu; Song Guo (Atmospheric Environment, 2023)

Effects of temperature on the time-dependent compression and shear behaviour of a soft marine clayey soil - Ze-Jian Chen; Run-Dong Zhao; Wen-Bo Chen; Pei-Chen Wu; Jian-Hua Yin; Wei-Qiang Feng (Engineering Geology, 2023)

Highly selective monoclonal antibody-based fluorescence immunochromatographic assay for the detection of fenpropathrin in vegetable and fruit samples - Zi-Hong Xu; Jun-Kai Wang; Qiu-Xiong Ye; Lin-Feng Jiang; Hao Deng; Jun-Fa Liang; Run-Xi Chen; Wei Huang; Hong-Tao Lei; Zhen-Lin Xu; Lin Luo (Analytica Chimica Acta, 2023)

Damming has changed the migration process of microplastics and increased the pollution risk in the reservoirs in the Shaying River Basin - Jiachen Shen; Xu Gu; Run Liu; Hongyu Feng; Dianpeng Li; Yan Liu; Xufei Jiang; Ge Qin; Shuqing An; Ning Li; Xin Leng (Journal of Hazardous Materials, 2023)

Trophinin-associated protein expression correlates with shorter survival of patients with glioma: a study based on multiple data fusion analysis - Yong Sun; Zhen Dong Liu; Run Ze Liu; Xiao Yu Lian; Xing Bo Cheng; Yu Long Jia; Bin Feng Liu; Yan Zheng Gao; Xinjun Wang (Molecular Biology Reports, 2022)

The decreased expression of GW2 homologous genes contributed to the increased grain width and thousand‑grain weight in wheat-Dasypyrum villosum 6VS·6DL translocation lines - Zhiyu Feng; Long Song; Wanjun Song; Zhongqi Qi; Jun Yuan; Run Li; Haiming Han; Huifang Wang; Zhaoyan Chen; Weilong Guo; Mingming Xin; Jie Liu; et al. (Theoretical and Applied Genetics, 2021)

EPG-recorded Feeding Behaviors Reveal Adaptability and Competitiveness in Two Species of Bemisia tabaci (Hemiptera: Aleyrodidae) - Shao-hua Lu; Jing-jing Li; Run-e Bai; Feng-ming Yan (Journal of Insect Behavior, 2021)

Prediction and Identification of Epitopes in the Emy162 Antigen of Echinococcus multilocularis - Ming-Quan Pang; Feng Tang; Hai-Jiu Wang; Ying Zhou; Li Ren; Run-Le Li; Hu Zhou; Chen-Fei Wan; Chuan-Chuan Liu; Cai-Rang Yangdan; Hai-Ning Fan (Acta Parasitologica, 2020)

Characterization of a Cu2+, SDS, alcohol and glucose tolerant GH1 β-glucosidase from Bacillus sp. CGMCC 1.16541 - Yi-Rui Yin; Peng Sang; Feng-Li Yang; Tao Li; Run-Feng Yang; Hong-Yan Liu; Zong-Long Luo; Wen-Jun Li; Li-Quan Yang (Antonie van Leeuwenhoek, 2020)

Physical Model Experimental Study on Spalling Failure Around a Tunnel in Synthetic Marble - Guo-Qiang Zhu; Xia-Ting Feng; Yang-Yi Zhou; Zheng-Wei Li; Lian-Jie Fu; Yong-Run Xiong (Rock Mechanics and Rock Engineering, 2020)

A role of age-dependent DNA methylation reprogramming in regulating the regeneration capacity of Boea hygrometrica leaves - Run-Ze Sun; En-Hui Zuo; Jin-Feng Qi; Yang Liu; Chih-Ta Lin; Xin Deng (Functional & Integrative Genomics, 2020)

Correlation between S100A11 and the TGF-β1/SMAD4 pathway and its effects on the proliferation and apoptosis of pancreatic cancer cell line PANC-1 - Yi-Fei Ji; Tao Li; Feng Jiang; Wen-Kai Ni; Cheng-Qi Guan; Zhao-Xiu Liu; Cui-Hua Lu; Run-Zhou Ni; Wei Wu; Ming-Bing Xiao (Molecular and Cellular Biochemistry, 2019)

β2-AR regulates the expression of AKR1B1 in human pancreatic cancer cells and promotes their proliferation via the ERK1/2 pathway - Ming-Bing Xiao; Dan-Dan Jin; Yu-Jie Jiao; Wen-Kai Ni; Jin-Xia Liu; Li-Shuai Qu; Cui-Hua Lu; Run-Zhou Ni; Feng Jiang; Wei-Chang Chen (Molecular Biology Reports, 2018)

Two flavonol glycosides from Liparis bootanensis - Shuai Huang; Run Wu; Feng Gao; Chunying Li; Xianli Zhou (Journal of Natural Medicines, 2018)

U–Pb zircon, geochemical and Sr–Nd–Hf isotopic constraints on age and origin of the intrusions from Wunugetushan porphyry deposit, Northeast China: implication for Triassic–Jurassic Cu–Mo mineralization in Mongolia–Erguna metallogenic belt - Kui-Feng Mi; Zhen-Jiang Liu; Rui-Bin Liu; Chun-Feng Li; Jian-Ping Wang; Run-Min Peng (International Geology Review, 2018)

Evaluation of the possible slip surface of a highly heterogeneous rock slope using dynamic reduction method - Guo-qing Chen; Run-qiu Huang; Feng-shou Zhang; Zhen-fei Zhu; Yu-chuan Shi; Jian-chao Wang (Journal of Mountain Science, 2018)

The In vitro/vivo Evaluation of Prepared Gastric Floating Tablets of Berberine Hydrochloride - Jun Ji; Xin He; Xiao-Lin Yang; Wen-Juan Du; Cheng-Long Cui; Ling Wang; Xue Wang; Chun-Feng Zhang; Chang-Run Guo (AAPS PharmSciTech, 2017)

High-order generalized screen propagator migration based on particle swarm optimization - Run He; Jia-Chun You; Bin Liu; Yan-Chun Wang; Shi-Guang Deng; Feng-Qi Zhang (Applied Geophysics, 2017)

Skarn mineralogy and its geological significance for the Tayuan (Cu–Mo)–Pb–Zn deposit, northern Daxinganling metallogenic belt - Chao Li; Tao Ren; Jian-Guo Huang; Run-Sheng Han; He-Jun Yin; Hong-Yang Zhou; Zhi-Hong Feng (Acta Geochimica, 2017)

XCI-escaping gene KDM5C contributes to ovarian development via downregulating miR-320a - Yi-Xi Sun; Yi-Xin Zhang; Dan Zhang; Chen-Ming Xu; Song-Chang Chen; Jun-Yu Zhang; Ye-Chun Ruan; Feng Chen; Run-Ju Zhang; Ye-Qing Qian; Yi-Feng Liu; Lu-Yang Jin; et al. (Human Genetics, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

A Brachypodium distachyon MAPKK Gene BdMKK6.2 Negatively Regulates Drought Stress Tolerance in Transgenic Tobacco Plants - Jiutong Sun; Run Zhou; Yaping Li; Wei Hu; Ding Qiu; Xiatian Wang; Qiong Wang; Zhijuan Feng; Lianzhe Wang; Yi Zhou; Guangyuan He; Guangxiao Yang (Journal of Plant Growth Regulation, 2016)

The Brachypodium distachyon BdWRKY36 gene confers tolerance to drought stress in transgenic tobacco plants - Jiutong Sun; Wei Hu; Run Zhou; Lianzhe Wang; Xiatian Wang; Qiong Wang; Zhijuan Feng; Yaping Li; Ding Qiu; Guangyuan He; Guangxiao Yang (Plant Cell Reports, 2015)

The influence of nitrogen on the development and accumulation of protein bodies in the developing endosperm of wheat caryopses - Fei Xiong; Xu-Run Yu; Liang Zhou; Jing Zhang; Bo Li; Jian Liu; Feng Wang; Ai-Sheng Xiong (Molecular Biology Reports, 2014)

Structural development of aleurone and its function in common wheat - Fei Xiong; Xu-Run Yu; Liang Zhou; Zhong Wang; Feng Wang; Ai-Sheng Xiong (Molecular Biology Reports, 2013)

Treatment of Furfural Residue by Solvent Extraction for Enzymatic Hydrolysis: Effect of Delignification on the Structure and Digestibility - Shao-Ni Sun; Xue-Fei Cao; Ming-Fei Li; Feng Xu; Run-Cang Sun (BioEnergy Research, 2013)

Characterization of Lignins Isolated with Alkaline Ethanol from the Hydrothermal Pretreated Tamarix ramosissima - Ling-Ping Xiao; Zheng-Jun Shi; Feng Xu; Run-Cang Sun (BioEnergy Research, 2013)

Unveiling the Structural Heterogeneity of Bamboo Lignin by In Situ HSQC NMR Technique - Jia-Long Wen; Bai-Liang Xue; Feng Xu; Run-Cang Sun (BioEnergy Research, 2012)

Screening Level of PAHs in Sediment Core from Lake Hongfeng, Southwest China - Jian-Yang Guo; Feng-Chang Wu; Liang Zhang; Hai-Qing Liao; Run-Yu Zhang; Wei Li; Xiao-Li Zhao; She-Jun Chen; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2011)